Pengaruh Model Pembelajaran Team Games Turnament (TGT) dengan Menggunakan Media Flashcard terhadap Kemampuan Kognitif dan Motivasi Belajar Biologi Siswa Kelas VII - Kasmayanti, Kasmayanti; Samsuri, Taufik; Safnowandi, Safnowandi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
The aim of this study was to determine the effect of the Team Games Tournament (TGT) learning model using Flashcard media on the cognitive abilities and motivation to learn Biology in class VII students at SMP Negeri 2 Praya Timur, Central Lombok Regency. This type of research is a quasy-experimental, with a research design using a post-test, Non-equivalent Control Group Design which is carried out in three meetings. The population in the study were all students of class VII SMP Negeri 2 Praya Timur. The research sample is class VII2 as the experimental class and class VII1 as the control class. Cognitive ability data was obtained using a test (post-test) which was carried out at the end of the learning process. The results showed that the average value of the classical class in the experiment (VII2) was 91,6%, and the completeness of the control class was 75%. Testing the cognitive ability hypothesis in this study uses the Polled Variance formula. On the results of cognitive abilities obtained a tcount of 3,000 and then consulted with a ttable of 2,0105 with dk = 48 at a significant level of 5%. Because tcount > ttable, it can be concluded that the Team Games Tournament learning model using Flashcard media has an effect on the Biological cognitive abilities of class VII students of SMP Negeri 2 Praya Timur. As for motivational data, a tcount of 34.46 was obtained with the same ttable. Because tcount > ttable, it can be concluded that the Team Games Tournament learning model using Flashcard media has an effect on motivation to study Biology in class VII of SMP Negeri 2 Praya Timur.